Foreign Experience of Pay in the Education System (Economic journal of Lesya Ukrainka Volyn National University, 2016)
In the article indicators of minimum and maximum wages in Ukraine and its neighboring countries are considered. Groups of kinds of economic activity, in which education got depending on salary (the first author’s method), and on the position in the ranking (by the second author’s method), are defined. Rating of eight countries in terms of wages in education in 2015 is formed. Determined that the best worried about educators in Poland, the worst – in Ukraine. Overseas education workers earn more than in our country: Polish – in 7,66 times, Hungarians – 6,45, Slovaks – 6,14, Romanians – 3,93, Russians – 3,11, Belarusians – 1,56, Moldovans – in 1,41 times.
Keywords: Ukraine, neighboring countries, wages, kind of economic activity, education